The importance of the hospital playroom. Issue 6 (2nd July 2021) - Stonehouse, David
Abstract : This article discusses the important role that playrooms provide for children when they are in hospital, either as inpatients, outpatients or even as visitors. Following an introduction highlighting the importance of play, the background to hospital playrooms will be identified. Links to the Nursing and Midwifery Council code will then be made, before discussing and highlighting the clear benefits of having designated and bespoke children's playrooms. However, there is a cautionary note: not all playrooms are being used for the purpose they were designed for. This other inappropriate use can prevent children from accessing playrooms when they need them, or even worse, are being subjected to clinical procedures within them. This will be highlighted and discussed. Finally, the role of the support worker and nursing associate will be made clear in how they can support children in accessing play opportunities within their clinical areas.